ESTIMATION OF HEAT DISSIPATION IN BROILER CHICKENS DURING THE FIRST TWO WEEKS OF LIFE - Ruvio, Jéssica Fantin; Schiassi, Leonardo; Araújo, Handrey Borges; Damasceno, Flávio Alves; Yanagi Junior, Tadayuki (REVISTA DE AGRICULTURA, 2017)
The objective of this work was to evaluate the heat dissipated in broiler chickens during the first two weeks of life and to estimate with infrared thermography the loss of sensible heat from birds. The environmental conditions were pre-established in wind tunnels using the automatic monitoring and control system, where only air temperature values were varied during each experimental week. Thus, the heat exchanges through convection and radiation of each animal were calculated by means of equations for the first and second week of life, and the temperature of the broilers was obtained by means of thermographic images. Based on the results, it has been found that the surface temperatures of the birds are correlated with air temperature and that they suffer greater heat dissipation when subjected to temperatures below their thermal comfort zone and also as growth develops.